Alasan Kasasi Penuntut Umum Terhadap Putusan Lepas dari Segala Tuntutan Hukum Dalam Perkara Bidang Kehutanan - Imam Chandra Lukmana (Sebelas Maret University, 2019)
Research discussed for the entreaty petition in proposed public prosecutor to prevent district court padangsidimpuan number 63/ Pid.Sus/2014/ PN.Psp On the basis of judex factie any judge in the matter of the felling of trees in the forest production owned by pt toba pulp lestari tbk . With the defendant samsul bahri simatupang and adam harahap in accordance with the provisions of article 253 kuhap. The judge in padangsidimpuan district court stated that the defendant was found guilty of committing the criminal act he was accused of, but the act is not a crime and release the defendant from all lawsuits. The method used is a normative legal research. The approach used in case approach. Sources of legal materials used are primary and secondary legal materials. An appeal to the fling by prosecutors against decisions out of all lawsuits or in forestry is in accordance with the provisions of article 253 kuhap paragraph (1) of KUHAP about examination in the cassation level done by Supreme Court, Because the district court judge padangsidimpuan on the basis of judex factie wrong judge said in its consideration do not judge or applied as proof should be particularly law allows and the right to do the tree legally.Keywords: Cassation, Freelance Decision, Any apply the law.